Advancements in Plant Molecular Biology and Genetics: Insights into Genetic Engineering, Genomics, and Crop Improvement - Shreya Singh (International Journal of Trends in Horticulture, 2025)
This comprehensive review explores the rapidly advancing fields of plant molecular biology and genetics, offering a thorough examination of contemporary research and innovative methodologies that contribute to a deeper understanding of plant development, improved crop productivity, and the mitigation of environmental challenges. Recent breakthroughs in genetic engineering, genomics, and transcriptomics are thoroughly analyzed to provide valuable insights into their practical applications for sustainable agriculture. The integration of cutting-edge tools and technologies in these areas has revolutionized our approach to studying plant biology, enabling the manipulation of genes to enhance desired traits. Additionally, advancements in genome sequencing and functional genomics have provided a clearer understanding of the molecular mechanisms underlying key processes such as stress tolerance, disease resistance, and nutrient uptake. Furthermore, the utilization of transcriptomics has enabled the identification of gene expression patterns associated with specific developmental stages and environmental responses, facilitating the development of more resilient and adaptable crop varieties. These developments are essential for tackling the problems caused by finite natural resources, climate change, and the rising demand for food worldwide. The synergy between plant molecular biology and genetics is paving the way for innovative solutions that promote the sustainable development of agriculture, fostering a more resilient and eco-friendly future for farming systems worldwide.
Keywords: CRISPR-Cas9; Genetic engineering; Genomics; Plant molecular biology; functional genomics; phenotypic plasticity; plant biotechnology; plant genetics; stress tolerance; transcriptomics